Faktor-Faktor Yang Mempengaruhi Efisiensi Investasi Pada Perusahaan Sektor Transportasi Periode 2018-2022 - Pratomo, Devina Agustin Goldie; Prajanto, Agung; Durya, Ngurah Pandji Mertha Agung (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
ABSTRACT Investment efficiency is thought to have several factors that influence it in this study the author uses four factors, namely the quality of financial statements (KLK), debt maturity, profitability performance, and company size. This research is a synthesis research that aims to analyze the impact of KLK, debt maturity, profitability performance, and company size on investment efficiency. Samples selected by purposive sampling were taken from companies in the transportation sector verified on the IDX during the period 2018 to 2022, with a total of 80 sample data. Data analysis was carried out using the PLS-SEM (Partial Least Squares-Structural Equation Modeling) method using WarpPLS 7.0 software. The results showed that KLK and Debt Maturity have no impact on investment efficiency, while Profitability Performance and Company Size affect investment efficiency.